NEW TRENDS IN THE DEVELOPMENT OF DATA PRESENTATION AND MANAGEMENT SYSTEMS. ANALYTICAL VIEW - Mintser, O. P.; Babintseva, L. Yu. (Medical Informatics and Engineering, 2022)
Background. IThe problems of the modern development of data presentation and management systems are analyzed. The amount, variety and speed of data are of particular value for management, science, and production. Today, big data is used for a number of tasks: improvement and acceleration of product development processes, ensuring high quality of work and service provision, high level of security, operational efficiency, etc. As the volume of big data grows, new opportunities open up. Special attention is paid to the new GO FAIR technology. The purpose of the study was to present the possibilities of using metatechnologies and metadata in health care. Materials and methods. A theoretical analysis and generalization of information on the use of metadata and metatechnologies in health care was carried out, as well as the systematization of research results on the specified topic using the following databases of scientific periodicals: Web of Science, PubMed, Scopus, ScienceDirect, OSF, ORE, IEEE, EBSCO. Classical methods of information search were applied at various stages of the research: selective, intuitive, inductive, deductive, and the method of bibliographic references. The methods of system analysis, structural analysis and design (SADT), data mining, cluster and factor analysis, system approach and methods of decision-making theory were used to process the received information. Results. The volume of data coming from various sources (video cameras, social networks, audio recordings, IoP devices) is constantly increasing, which leads to the emergence of new big data management systems. The most important step for continuous software delivery is continuous integration. Cloud computing has advantages for global analysis on longer time scales, where latency is not a concern. Health data management is tasked not only with organizing medical data, but also with integrating and analyzing it to make patient care more efficient and to obtain information that can improve medical outcomes while protecting data privacy and security. Among modern areas of data management systems, the GO FAIR platform is considered in detail. Conclusions. The constant avalanche-like growth of data determines the continuous growth of data management problems. Good data management benefits patients, providers and insurers, and has far-reaching implications for the health of the entire population. Among modern directions of data interest, which is a management technology without user intervention, in fact, one of the first steps towards the formation of a digital infrastructure.